Comparison of renewable integration schemes for AC railway power supply system - Nakaret Kano; Zhongbei Tian; Nutthaka Chinomi; Stuart Hillmansen (IET Electrical Systems in Transportation)
Abstract To achieve the UK net‐zero emissions target by 2050, transformations to decarbonise the energy system will be essential. A transition from generating electricity by burning fossil fuel to renewable energy sources (RESs) is one of the most effective ways, in addition to customer transformation, in which people are willing to participate to reduce energy consumption. The railway sector accounts for 0.5% of carbon emissions in the United Kingdom. In order to meet the net‐zero goal, more railway routes must be electrified, as only 38% of railway routes are electrified at present. Furthermore, clean energy is necessary. Therefore, schemes for integrating RESs into the AC high‐speed railway power supply system are proposed and simulated in a case study. Power losses in the power system are comprehensively studied and compared. Owing to the fluctuation of traction load, the power quality issue is inevitable. Thus, the voltage unbalance factor is adopted to measure the severity of the imbalance. The results from the case study demonstrate that the proposed scheme in which the RES is connected to a three‐phase railway power network generates the smallest power losses among all proposed schemes. Moreover, it also requires lower investment expenditure and provides the most significant cost saving in the long run. The results also reveal that the VUFs of all schemes based on a 400 kV transmission system are below the United Kingdom's stringent limit of 1.5%. Furthermore, the CO2 emissions are reduced significantly with RES integration by half for the case study with the 120 MW RES. Although the other proposed schemes had higher losses and lifetime costs, the differences are not significant. Each scheme has its advantages and disadvantages. Several factors need to be considered to choose the suitable scheme, such as the size of land available etc.